THE ROLE OF LINGUISTICS IN UNDERSTANDING LANGUAGE STRUCTURE AND SOCIAL INTERACTION - Rahmatika Aini, Miza (Jurnal Multidisipliner Bharasumba, 2025)
Linguistics also examines the relationship between language and the wider social context, including how language shapes and is influenced by structures of power, social status and culture. From the perspective of phonology, it explores the patterns of sounds in language and how they shape meaning and influence understanding and communication. Meanwhile, in morphology, attention is focused on the internal structure of words and the process of word formation in language. Syntax addresses the rules that govern how words are combined to form meaningful sentences. Semantics, on the other hand, focuses on the study of meaning and how meaning is derived in communication. Pragmatics examines language use in social and interactional contexts, revealing how individuals interpret meaning based on the situation and the speaker's intentions. Sociolinguistics extends this scope by analyzing the relationship between language and social factors, while psycholinguistics looks at the mental processes involved in language production and comprehension. Knowledge of linguistics provides greater insight into the dynamics of human communication and the ways in which language plays a role in shaping understanding of the world.